Biochar: Harnessing Nature’s Charcoal for Sustainability - Shaikh Faisal Suleman Ashfaq; Fakhruddin Choudhary (International Journal of Environmental Noise and Pollution Control, 2024)
As we all know, CO2 is a greenhouse gas that traps the largest amount of heat from the air, thus causing our planet Earth to get warmer and warmer. Humans raised CO2 levels over the last two centuries years, leading to climate change. India, ranked fourth globally in emitting greenhouse gases (GHGs), sees a significant portion of emissions from the agriculture sector. Burning crop stubble in states like Punjab and Haryana worsens air pollution. Transitioning to cleaner practices like biochar is vital to reduce carbon emissions. Researchers are keen on biochar recently for its agricultural and environmental advantages. It enhances soil fertility, boosts crop productivity, and acts as a valuable tool for climate mitigation by capturing carbon in the soil. Even though scientists have studied the chemical, biological, and technical parts of biochar, using it effectively in real life is still far away. To make biochar work, we need to pay more attention to how people and organizations use it, not just the science stuff. This Paper Continues to debate about the benefits of biochar and the production of biochar using IOT sensors.
Keywords: Biochar; Environmental; charcoal; pyrolysis; thermocouple